Anesthetic Considerations of Patient with Parry Romberg Syndrome - Sussan Soltani Mohammadi (Case Reports in Clinical Practice, 2018)
Parry Romberg syndrome is a rare progressive degenerative disease characterized by unilateral atrophy affecting the skin, connective tissue, muscle, and bone, typically occurs in children and young adults. The end result is facial asymmetry associated with other skin, dental, visual, cardiovascular, and neurological disorders that ceases without apparent cause after a highly variable period. Inconsistency in the pattern of atrophy and multisystem involvement make intraoperative anesthetic management of these patients a challenge for anesthesiologists. We present a case of Parry Romberg syndrome and her associated clinical findings with specific attention to the anesthetic consideration of this disease.